2008
DOI: 10.1080/00071660802290424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of less intensive rearing conditions on litter characteristics, growth performance, carcase injuries and meat quality of broilers

Abstract: 1. The objective was to compare the effect of two litter types (wheat straw and wood shavings) and two different rearing conditions (Treated and Control) on welfare indicators, broiler performance, carcase injuries, particularly hock and foot pad dermatitis (FPD), litter characteristics and meat quality. 2. Treated conditions were characterised by a low stocking density (11 birds/m(2)), short photoperiod (16 h light: 8 h dark) and a large amount of litter (3 to 4.5 kg/m(2), respectively, for wheat straw or woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 18 publications
3
30
1
6
Order By: Relevance
“…It is well known that broiler chickens are usually confront a multitude of stressors, including human handling disturbance and adverse housing environment (e.g., heat, cold, noise, crowding and wet litter). The responses against these stressors are associated with several serious welfare problems (Hocking et al, 2005;Meluzzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that broiler chickens are usually confront a multitude of stressors, including human handling disturbance and adverse housing environment (e.g., heat, cold, noise, crowding and wet litter). The responses against these stressors are associated with several serious welfare problems (Hocking et al, 2005;Meluzzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of FPD scores obtained in the present trial was 546 zero and no differences were found in relation to TM meal 547 utilization. This is a positive result, since a low prevalence and 548 severity of FPD is highly desirable as far as health of birds and 549 product quality are concerned (Meluzzi et al, 2008). performance, carcass and meat traits.…”
mentioning
confidence: 99%
“…These lesions, also known as "ammonia burns", are caused by the combination of moisture and high ammonia content of the litter (Kjaer et al ., 2006). Knee dermatitis has been positively correlated with footpad dermatitis (Meluzzi et al ., 2008). Footpad and knee dermatitis are associated with high moisture and ammonia content.…”
Section: Discussionmentioning
confidence: 99%